Variations in drug-related problems detected by multidisciplinary teams in Norwegian nursing homes and home nursing care - Siri A. Devik; Rose Mari Olsen; Inger Lise Fiskvik; Terje Halbostad; Tone Lassen; Natalia Kuzina; Ingela Enmarker (Scandinavian Journal of Primary Health Care, 2018)
Objective: Traditionally, nursing homes have been associated with suboptimal drug therapy and drug-related problems (DRPs). In contrast, less is known about drug safety in homecare. The aim of this study was to describe and compare DRPs in older persons across two care settings: nursing homes and home nursing care. Design: Cross-sectional study using descriptive and inferential statistics. Setting: Nursing homes (n = 5) and home nursing care units (n = 8) across nine municipalities in the middle of Norway. Participants: Multidisciplinary medication reviews for 61 nursing home residents and 93 patients receiving home nursing care performed over the 2013–2014 period, were mapped and examined (N = 154). Main outcome measures: DRPs classified by a Norwegian Classification Tool. Results: In all, 740 DRPs were detected in the total sample, 227 in nursing homes and 513 in home nursing care. DRPs were significantly higher among patients receiving home-based care (Mean =5.5) compared to patients in nursing homes (Mean =3.7, p = 0.002). Among the problem categories, the need for additional drug was most frequent in nursing homes (p = 0.001), while documentation discrepancies reached the highest numbers in patients receiving home nursing care (p = 0.000). Additionally, patients in home nursing care had more problems concerning adverse reactions (p = 0.060); however, this was not statistically significant. Differences in DRP categories leading to changes in the patients’ medication lists were also discovered. Conclusions: The frequency of unclear documentation and adverse reactions found in the homecare setting is alarming. This is an important issue given the trend in aged care towards caring people in their own homes. Further research is warranted to explore how different care settings may influence the safety of pharmacotherapy for older persons.Key Points Drug related problems are a significant cause of concern among patients receiving home nursing care as well as for patients living in nursing homes. The findings of this study showed that: •Significantly more DRPs were detected among patients receiving home nursing care than patients living in nursing homes. •While patients living in nursing homes were often undermedicated, documentation discrepancies were more frequent in home nursing care. •DRP categories leading to changes on the medication lists differed between the settings.